Accessibility to safe and hygienic sanitation facilities and the prevalence of open-air defecation among the school going adolescents in rural Puducherry - Surabhi Gitika Priya; Jayalakshmy Ramakrishnan; Premkumar Ramasubramani; Jeby Jose Olickal; Sadhana Subramanian; Subitha Lakshminarayanan (Elsevier, 2023)
Purpose: Despite various government initiatives to promote sanitary practices, open-air defecation (OAD) practice among school-going adolescents in rural India is still evident. The unhygienic sanitary practices propagate a vicious cycle of disease transmission affecting their nutritional status. The study aims to find the accessibility to safe, hygienic sanitation facilities and the prevalence of OAD open-air defecation practice, and the factors associated with it among the school-going adolescents in rural Puducherry. Methods: It was a cross-sectional analytical study conducted among school-going adolescents in a rural Puducherry. Information on the sociodemographic, behavioural, and nutritional characteristics was collected using a pre-tested questionnaire in EpiData Version.3.03. Haemoglobin estimation was done using a portable hemoglobinometer and anaemia was categorized as per the WHO guidelines. Data analysis was done using SPSS version 19. Results: Out of the 773 school-going adolescents, 74.6% (95% CI:73.4-80.2) had accessibility to safe and hygienic-sanitary toilets and 35.2% (95% CI: 31.9-38.6%) had the practise of OAD. Haemoglobin was estimated in 352 study participants. Among adolescents practising OAD, 87 (75%) were found to be anaemic compared to 143 (60.6%) among those without OAD practice. Statistically significant proportions of adolescents living in kutcha houses were practising OAD compared to semi-pucca or pucca houses. As per the national programme, 88.9% and 86.3% of the study participants consumed IFA and deworming tablets, respectively. Conclusion: Due to the inaccessibility to safe and hygienic sanitation facilities and the lack of knowledge on the same, the school-going adolescents practised open-air defecation.